Fraud in Financial Institutions: The Contribution of Bengkulu Bank Internal Audit - Karona Cahya Susena; Kamaludin; Rina Suthia Hayu; Muhammad Rusdi (GoAcademica Research & Publishing, 2023)
This research explores the key role internal audit plays in mitigating fraud risk. We revealed that internal audit actively examines financial transactions, evaluates internal control procedures, and identifies potential fraud risks. With internal audit's strong competence and team structure, they are at the forefront of protecting banks from fraud risk. Risk evaluation is an essential step in fraud prevention, and this research highlights how internal audit continuously conducts risk evaluations to identify the most vulnerable areas. A fast and effective fraud detection process is also emphasized in this study, where Bank Bengkulu's internal audit has built sophisticated audit tools and techniques to detect suspicious patterns in real-time. While internal audit plays a crucial role in fraud prevention, the research also identified several obstacles and challenges internal audit teams face. In particular, technological developments and increasingly sophisticated fraud demand proactive measures and investment in resources, education, and training. This research confirms that the internal audit at Bengkulu Bank significantly contributes to maintaining the integrity and stability of the bank's operations. In the face of increasingly complex fraud threats, constant efforts in developing internal audit capabilities are essential to protect banks from fraud risks.